2010
DOI: 10.1093/nar/gkq338
|View full text |Cite
|
Sign up to set email alerts
|

Decoding accuracy in eRF1 mutants and its correlation with pleiotropic quantitative traits in yeast

Abstract: Translation termination in eukaryotes typically requires the decoding of one of three stop codons UAA, UAG or UGA by the eukaryotic release factor eRF1. The molecular mechanisms that allow eRF1 to decode either A or G in the second nucleotide, but to exclude UGG as a stop codon, are currently not well understood. Several models of stop codon recognition have been developed on the basis of evidence from mutagenesis studies, as well as studies on the evolutionary sequence conservation of eRF1. We show here that … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
26
0

Year Published

2012
2012
2018
2018

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 36 publications
(33 citation statements)
references
References 50 publications
7
26
0
Order By: Relevance
“…A study by von der Haar and colleagues showed that a V68A mutation caused a bias against stop codons with an adenine in position three, consistent with our data and the assignment of this residue near cavity three (Merritt et al 2010). However, another study reported that this mutation allowed termination to remain similar to wildtype eRF1 in S. cerevisiae cells (Bertram et al 2000).…”
Section: Discussionsupporting
confidence: 92%
“…A study by von der Haar and colleagues showed that a V68A mutation caused a bias against stop codons with an adenine in position three, consistent with our data and the assignment of this residue near cavity three (Merritt et al 2010). However, another study reported that this mutation allowed termination to remain similar to wildtype eRF1 in S. cerevisiae cells (Bertram et al 2000).…”
Section: Discussionsupporting
confidence: 92%
“…The quantitative analysis performed here contributes to a more differentiated view of the roles of all of these four factors. Table I), and indeed previous work has indicated that these four proteins have a range of non-translational roles in the cell (Amrani et al, 1997;Valentini et al, 2002;Cole and Scarcelli, 2006;Urakov et al, 2006;Halls et al, 2007;Pittman et al, 2009;Merritt et al, 2010). On this basis, we classify Dbp5, Ded1, Pab1, and Hyp2 as multifunctional translation factors.…”
Section: Control By Additional (Multifunctional) Translation Factorssupporting
confidence: 69%
“…The detailed study of a large collection of sup45 mutants accomplished recently confirms the last point of view [48].…”
Section: Discussionsupporting
confidence: 61%